Love your neighbor and yourself : a Jewish approach to modern personal ethics - Dorff, Elliot N. (Philadelphia, PA : Jewish Publication Society, 2006)
Now in Paperback!A leading ethicist suggests ways to take the moral high road in one?s personal life. In this topically relevant book on modern ethical issues, Dorff focuses on personal ethics, Judaism?s distinctive way of understanding human nature, our role in life, and what we should strive to be, both as individuals and as members of a community. Dorff addresses specific moral issues that affect or personal lives: privacy, particularly at work as it is affected by the Internet and other modern technologies; sex in and outside of marriage; family matters, such as adoption, surrogate motherhood, stepfamilies, divorce, parenting, and family violence; homosexuality; justice, mercy, and forgiveness; and charitable acts and social action.
Judaism and ethics. Ethics versus morals ; The variety of ethical theories ; Jewish ethics ; Jewish morals ; Not in the heavens -- Privacy. The internet and privacy ; The values and concepts motivating a concern for privacy ; Contrasting American and Jewish interests in privacy ; Intrusion ; Disclosure ; Proposals for protecting against intrusion and disclosure -- "This is my beloved, this is my friend": sex and the family. Sexual relations: fundamental concepts and values ; Sex within marriage ; Nonmarital sex ; Homosexuality ; Making sex meaningful, joyful, and holy -- Parents and children. Filial duties: the perspective of Jewish classical sources ; Caring for elderly parents in today's world ; Parental duties: applying Jewish classical sources to contemporary circumstances -- Family violence. Types of abuse and their Jewish legal status ; Acknowledging family violence within our community ; Witnesses to the act or results of abuse ; The abused party: making one's way out of an abusive situation ; The abuser ; The role of rabbis, educators, and lay leaders ; Reconnecting with God's image within us -- The elements of forgiveness. God's role in forgiveness: the guidance of the prayer book ; Obstacles to asking for forgiveness ; Obstacles to forgiving ; Factors promoting forgiveness ; Pardon, forgive, and reconcile ; The process of return (Teshuvah): becoming worthy of forgiveness -- Hope and destiny. God ; Individuals and community ; Individual destiny ; Communal destiny -- Appendix: The interaction of Judaism with morality: defining, motivating, and educating a moral person and society. Religious factors motivating immorality ; Judaism's contributions to morality: definition of moral norms, moral motivation, and moral education ; Study ; Law.
Includes bibliographical references (pages 347-359) and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Jewish ethics; Conduct of life; Jewish way of life; Jewish philosophy; RELIGION -- Judaism -- Theology; Conduct of life; Jewish ethics; Jewish philosophy; Jewish way of life; Electronic books